2023
DOI: 10.3390/ani13132072
|View full text |Cite
|
Sign up to set email alerts
|

Profitability and Cost Analysis for Contract Broiler Production in Turkey

Abstract: This study uses the data obtained from 63 broiler farms engaged in contract farming in Akhisar, Turkey. The average feed conversion ratio in the broiler farms is 1.75, the average live weight 2.25 kg, and the mean market age 38.9 days. The feed conversion rate and the income generated are highly correlated (r = −0.76). The production index is 313.4. According to this production index value, 47.6% of the enterprises are below the average production index. It is highest when the marketing age is greater than 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, the authors reported no expenditure towards repairing and cleaning. Karaman et al (2023) [32] found that despite being heavily influenced by the mortality rate and feed conversion ratio, contract broiler production in Turkey remained profitable. Nevertheless, the authors noted that heating cost had the largest share of the total cost, with litter cost following closely behind.…”
Section: Financial Profitability Of Safe Broiler Productionmentioning
confidence: 99%
“…However, the authors reported no expenditure towards repairing and cleaning. Karaman et al (2023) [32] found that despite being heavily influenced by the mortality rate and feed conversion ratio, contract broiler production in Turkey remained profitable. Nevertheless, the authors noted that heating cost had the largest share of the total cost, with litter cost following closely behind.…”
Section: Financial Profitability Of Safe Broiler Productionmentioning
confidence: 99%
“…In contract broiler production, the cost of energy may be preponderant for growers. Providing heating and electrical energy to the farm may represent a cost that ranges between EUR 0.06 [10] and EUR 0.32 [11] per broiler, depending on the considered context. In contract broiler production, thermal and electrical energy account for 25% and 12% of the total variable costs for the grower, respectively [11].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…Providing heating and electrical energy to the farm may represent a cost that ranges between EUR 0.06 [10] and EUR 0.32 [11] per broiler, depending on the considered context. In contract broiler production, thermal and electrical energy account for 25% and 12% of the total variable costs for the grower, respectively [11]. The energy consumption due to climate control also has a negative impact from the environmental point of view.…”
Section: Introduction 1backgroundmentioning
confidence: 99%